PENGARUH TERAPI SENAM HIPERTENSI TERHADAP TEKANAN DARAH PADA LANSIA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BANYUMULEK - Ageng Abdi Putra; I Gusti Ayu Mirah Adhi; Lusi Nafitasari; Suhartiningsih; Nurhayati; Sri Masdiningsih Utami (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Hypertension is a condition where the systolic blood pressure in a person's body is more than or equal to 140 mmHg and the distolic blood pressure is more than 90 mmHg (Ministry of Health 2019). The NTB Health Service (2020) reports that hypertension sufferers aged ≥ 15 years in NTB Province are estimated at 293,106. One of the non-pharmacological treatments for treating hypertension is hypertension exercise. Exercise also stimulates the release of endorphin hormones. The aim of this research is to see the effect of hypertension exercise on reducing blood pressure in elderly people with hypertension in the Banyumulek Community Health Center working area. This research is quantitative research with a pre-experimental one group pre test post test design method, the number of samples used in this research was 37 respondents, the sampling technique used was purposive sampling. The instruments used are measurement tools and SOPs for measuring blood pressure, as well as data analysis using the paired Wilcoxon test. The results of the study showed that yoga exercise had the effect of lowering blood pressure in the elderly in the Banyumulek health center working area, proven by sig value analysis. (2-tiled) is 0.000 because the sig value (2-tiled) 0.000 is smaller than 0.05 (P<0.05). The conclusion of this research is that there is an effect of hypertension exercise on reducing blood pressure in the elderly in the Banyumulek Community Health Center working area.